Strategi Meningkatkan Minat Baca Masyarakat melalui Program Perpustakaan Berbasis Inklusi Sosial: Studi Kasus Dinas Perpustakaan dan Arsip Daerah Kota Bima - Sabil, Novia Ibni; Iskandar, Iskandar; Mathar, M. Quraisy (Literatify: Trends in Library Developments, 2026)
This study investigates strategies to enhance community reading interest through the Social Inclusion-Based Library Program at the Regional Library and Archives Office of Bima City. Using a qualitative descriptive approach, the research describes strategies applied to increase reading interest, the implementation of social inclusion programs, and challenges encountered. Data were collected through observation, interviews, and documentation from both primary and secondary sources. The analysis followed data reduction, presentation, and conclusion drawing. The findings indicate that the library applies four key strategies: technical training and service equalization, service maximization, promotion, and collaboration. The implementation focuses on two main principles—community welfare through literacy and equitable access to library services. Internal challenges include communication gaps and limited facilities, while external ones involve low public awareness and weak collaboration networks. Overall, the program contributes to improving community motivation to read, enhancing skills, and strengthening the library’s role as a social learning center and driver of sustainable literacy movements.